Check the Blood Pressure!: An Educational Tool for Anesthesiology Trainees Converting Epidural Labor Analgesia to Cesarean Delivery Anesthesia. Issue 6 (April 2020) - Zheng, Xiwen; Siddiqui, Zuhair; Anderson, Nick; Chen, Chen-Miao; Chatterji, Madhabi; Smiley, Richard; Landau, Ruth; Meng, Marie-Louise
Abstract : Recognition and treatment of maternal hypotension during epidural anesthesia administration for intrapartum cesarean delivery preserves maternal-fetal perfusion. A case that required quality assurance review uncovered lapses in maternal hemodynamic monitoring during the transition to intrapartum cesarean delivery anesthesia. To address this, a practice outline was designed for trainee's education describing intrapartum epidural dosing for cesarean delivery and adequate blood pressure monitoring. The time-lapse between epidural dosing and subsequent blood pressure was evaluated before and after the introduction of our educational tool. The time-lapse between blood pressure measures decreased to <10 minutes (10.78–13.92 vs 8.8–9.76 minutes).